A case of localized bullous scleroderma - A. L. Bakulev; E. M. Galkina; A. V. Karakaeva; M. V. Litvinenko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Bullous scleroderma is a rare type of the focal form of the disease mainly affecting the skin and characterized by induration and sclerosis foci as well as subepidermal blisters containing a transparent matter. The article describes a case study of bullous scleroderma in an adult woman with localized skin eruptions in the area of the left breast, which were completely regressed after a standard therapy with the use of drugs having an effect on collagen synthesis.